Unnecessary work tasks and mental health: a prospective analysis of Danish human service workers - Ida EH Madsen; Manisha Tripathi; Marianne Borritz; Reiner Rugulies (Nordic Association of Occupational Safety and Health (NOROSH), 2014)
OBJECTIVES: According to the "stress-as-offense-to-self" perspective, work tasks that are considered unnecessary or unreasonable - so-called "illegitimate work tasks" - are likely to elicit stress-reactions. Previous studies, mostly cross-sectional, have shown that illegitimate tasks are associated with increased self-reported stress, cortisol, and counterproductive work behavior. In this article, we examine the prospective association between unnecessary work tasks, one type of illegitimate work tasks, and mental health among Danish human service workers. Further, we explore whether this association is modified by sex, age, occupational position, and baseline mental health status. METHODS: The data were obtained from self-administered questionnaires from 1351 Danish human service workers in three waves of data-collection during 1999-2005. We measured unnecessary work tasks by a single item, and assessed mental health using the 5-item mental health inventory from the Short form 36 questionnaire. We analyzed data using multi-level modeling, adjusting for potential confounding by sex, age, cohabitation, occupational position, and baseline mental health. RESULTS: Unnecessary work tasks were prospectively associated with a decreased level of mental health. This association was stronger for employees with poor baseline mental health and tended to be more pronounced among older employees. Among participants with poor baseline mental health, the association was explained by neither psychological demands nor decision latitude. CONCLUSIONS: Our findings suggest that the prevention of unnecessary work tasks may benefit employee mental health, particularly among employees with pre-existing mental health problems.